Study of Effects of Formalin Exposure in Dissection Hall on Pulmonary Function Tests of Medical Students (Indian Journal of Public Health Research & Development, 2020)
Introduction: Formalin is being used for preservation of biological specimens including cadavers inlaboratories and dissection halls of medical colleges worldwide. It is used as disinfectant and preservativesolution in Anatomy mortuaries, Pathological laboratories, Hospitals and plastic industries. Exposure occursmainly by inhalation. This study was planned to assess effects of exposure to formalin on lung function ofmedical students.Method: Spirometry was done before exposure, after acute exposure and at end of academic year. Resultswere analysed.Results: There was significant decrease in values of FVC, FEV1,FEF25-75, FEF.2-1.2 and MVV (p0.05). Thoughthe PEFR was decreased after acute exposure it was not up to a statistically significant level (p>0.05).Thevalues of FVC, FEV1, FEF25-75, FEF.2-1.2 and MVV which were reduced significantly after acuteexposure came to normal after chronic exposure. The FEV1/FVC ratio was almost same (p>0.05). PEFRwas significantly increased (p
Keywords: Formalin exposure Dissection hall Medical students Lung function.